Phenotypic and Transcriptomic Responses of Campylobacter jejuni Suspended in an Artificial Freshwater Medium - Trigui, Hana; Lee, Kristen; Thibodeau, Alexandre; Lévesque, Simon; Mendis, Nilmini; Fravalo, Philippe; Letellier, Ann; Faucher, Sébastien P. (Frontiers in Microbiology, 2017)
Campylobacter jejuni is the leading cause of campylobacteriosis in the developed world. Although most cases are caused by consumption of contaminated meat, a significant proportion is linked to ingestion of contaminated water. The differences between C. jejuni strains originating from food products and those isolated from water are poorly understood. Working under the hypothesis that water-borne C. jejuni strains are better equipped at surviving the nutrient-poor aquatic environment than food-borne strains, the present study aims to characterize these differences using outbreak strains 81116 and 81-176. Strain 81116 caused a campylobacteriosis outbreak linked to consumption of water, while strain 81-176 was linked to consumption of raw milk. CFU counts and viability assays showed that 81116 survives better than 81-176 at 4°C in a defined freshwater medium (Fraquil). Moreover, 81116 was significantly more resistant to oxidative stress and bile salt than strain 81-176 in Fraquil. To better understand the genetic response of 81116 to water, a transcriptomic profiling study was undertaken using microarrays. Compared to rich broth, strain 81116 represses genes involved in amino acid uptake and metabolism, as well as genes involved in costly biosynthetic processes such as replication, translation, flagellum synthesis and virulence in response to Fraquil. In accordance with the observed increase in stress resistance in Fraquil, 81116 induces genes involved in resistance to oxidative stress and bile salt. Interestingly, genes responsible for cell wall synthesis were also induced upon Fraquil exposure. Finally, twelve unique genes were expressed in Fraquil; however, analysis of their distribution in animal and water isolates showed that they are not uniquely and ubiquitously present in water isolates, and thus, unlikely to play a major role in adaptation to water. Our results show that some C. jejuni strains are more resilient than others, thereby challenging current water management practices. The response of 81116 to Fraquil serves as a starting point to understand the adaptation of C. jejuni to water and its subsequent transmission.